Approach to Iconography of Nike in Greek Art - Rodríguez López, María Isabel (Eikón / Imago, 2013)
The image of Victory, the winged messenger associated with success and power, is one of the most evoked issues by artists of all times. The present paper provides a diachronic summary of its iconography from Archaic Greek to the representations in late Hellenistic Art. We study the formal and iconographic evolution and also suggest the semantic connotations of such a significant icon.